Cluster-randomised trial evaluating a complex intervention to improve mental health and well-being of employees working in hospital - a protocol for the SEEGEN trial - Nadine Mulfinger; Anja Sander; Felicitas Stuber; Regina Brinster; Florian Junne; Ronald Limprecht; Marc N. Jarczok; Tanja Seifried-Dübon; Monika A. Rieger; Stephan Zipfel; Martin Peters; Maja Stiawa; et al. (BMC, 2019)
Abstract Background Health care employees in Germany and worldwide are exposed to a variety of stressors. However, most of the hospitals in Germany lack a systematic workplace health management. Thus, this study aims at the evaluation of the effects of a behavioural as well as organisational (´complex´) intervention on the mental health and well-being of hospital staff. Methods Mental health in the hospital workplace (SEElische GEsundheit am Arbeitsplatz KrankeNhaus - SEEGEN) is an unblinded, multi-centred cluster-randomised open trial with two groups (intervention group (IG) and waitlist control group (CG)). Study participants in the intervention clusters will receive the complex intervention; study participants in the waitlist control clusters will receive the complex intervention after the last follow-up measurement. The intervention consists of five behavioural and organisational intervention modules that are specifically tailored to hospital employees at different hierarchical and functional levels. Hospital staff may select one specific module according to their position and specific needs or interests. Towards the end of the intervention roundtable discussions with representatives from all professional groups will be held to facilitate organisational change. Primary outcome is the change in emotional and cognitive strain in the working environment, from baseline (T0) to 6 month-follow up (T1), between IG and CG. In addition, employees who do not participate in the modules are included in the trial by answering shorter questionnaires (cluster participants). Furthermore, using mixed methods, a process evaluation will identify uptake of the intervention, and mediators and moderators of the effect. Discussion There seems to be growing psychological strain on people working in the health care sector worldwide. This study will examine whether investing directly in the hospital staff and their interpersonal relationship may lead to measurable benefits in subjective well-being at the workplace and improved economic performance indicators of the hospital. In case of a positive outcome, health promotion strategies looking at behavioural as well as organisational components within the hospital may gain additional importance, especially in regard of the growing financial pressure within the health sector. Trial registration DRKS The SEEGEN study is registered at the German Clinical Trial Register (DRKS) under the DRKS-ID DRKS00017249. Registered 08 October 2019, URL. https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00017249.